If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (2X + -1)(3X + 2) Reorder the terms: y = (-1 + 2X)(3X + 2) Reorder the terms: y = (-1 + 2X)(2 + 3X) Multiply (-1 + 2X) * (2 + 3X) y = (-1(2 + 3X) + 2X * (2 + 3X)) y = ((2 * -1 + 3X * -1) + 2X * (2 + 3X)) y = ((-2 + -3X) + 2X * (2 + 3X)) y = (-2 + -3X + (2 * 2X + 3X * 2X)) y = (-2 + -3X + (4X + 6X2)) Combine like terms: -3X + 4X = 1X y = (-2 + 1X + 6X2) Solving y = -2 + 1X + 6X2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -2 + 1X + 6X2
| 2(-1)+5y=3 | | 13-7x=-(5-11x) | | 13-7x=5-11x | | 25=5(a-7) | | 5v-18=10v-53 | | 3(-5x-17)=3 | | 2(4y)-y=-1 | | 8-3=2(x+1) | | B=3/4(21-b) | | (n+7)(11n-2)=18n(2n+1) | | A=21-b | | 4/3(-5.25) | | f(4)=2.0x^2+7.6x^4+5.0 | | f(x)=2.0x^2+7.6x^4+5.0 | | F=5(10)+18 | | 9w+(-31)= | | 11n^2+21n-14=0 | | -9/5x=27 | | q=m*c*changeT | | F=5(4)+18 | | F=5(2)+18 | | X+5a=29+ax-6a | | 2n=-28n-3 | | V=XLT | | 2x-x+112=16x+112 | | 3/e=3/4 | | 5n-6=18 | | 2y-3+y+6=12 | | F=5(3)+11 | | F=5(5)+11 | | 2x+8x+4+x=180 | | 2q+2q-48=180 |